Evaluating the Feasibility of a Pilot Exercise Intervention Implemented Within a Residential Rehabilitation Unit for People With Severe Mental Illness: GO HEART: (Group Occupational Health Exercise and Rehabilitation Treatment) - Korman, Nicole H.; Shah, Shelukumar; Suetani, Shuichi; Kendall, Karen; Rosenbaum, Simon; Dark, Frances; Nadareishvili, Ketevan; Siskind, Dan (Frontiers in Psychiatry, 2018)
Purpose: People with severe mental illness are sedentary, have high cardio-metabolic risks and significantly reduced life expectancy. Despite considerable data regarding positive physical and mental health outcomes following exercise interventions, implementation and evaluation of real-world programs is lacking. The primary aim of this study was to assess the feasibility of an exercise intervention implemented by exercise physiology (EP) students within a residential rehabilitation unit for residents with severe mental illness, together with assessment of a range of secondary physical and mental health outcomes pre- and post- the intervention. Design: Single arm, prospective pilot study evaluating outcomes pre- and post- a 10 week intervention. Method: Inactive people with severe mental illness participated in a mixed aerobic and resistance exercise intervention, three times per week for 10 weeks. Data was obtained from a sample of 16 residents with severe mental illness; primary diagnosis schizophrenia (n= 12). Primary outcomes were feasibility as assessed using recruitment, retention and participation rates, as well as reasons for withdrawal and amount of exercise achieved. Secondary outcomes included a range of physical and mental health outcomes. Functional exercise capacity was measured by the six-minute walk test. Metabolic data was obtained from anthropometric measurements, blood pressure, fasting cholesterol and blood sugar levels. Physical activity levels and mental health was assessed by self-administered questionnaires. Results: Broad level acceptance of the program: high recruitment (81%), retention (77%) and participation (78%) rates were observed. Promising improvements in functional exercise capacity, volume of exercise, and negative symptoms was demonstrated in those who completed. Conclusions: Exercise interventions delivered by EP students in a residential rehabilitation setting for people with SMI are feasible; group setting, supervision and choice for engagement are important considerations. Evaluation of longitudinal, multi site studies, with the addition of dietary interventions within residential rehabilitation units are warranted. Addressing cost feasibility and cost effectiveness of such programs is recommended. The trial was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) number,